Impact of perception and assessment of consumers on willingness to pay for upgraded fresh pork: An experimental study in Vietnam - Ngo, Hai Hoang Tuan; Dang-Xuan, Sinh; Målqvist, Mats; Pham-Duc, Phuc; Nguyen-Hong, Phi; Le-Thi, Hang; Nguyen-Viet, Hung; Le, Trang T. H.; Grace, Delia; Lindahl, Johanna F.; Unger, Fred (Frontiers in Sustainable Food Systems, 2023)
Traditional pork shops play an essential role in delivering pork, the most popular food in Vietnam, to consumers. Studies have shown the need for investment in training and equipment to improve the safety of pork sold at traditional shops. However, it remains unclear how consumer perceived improvement to the hygiene in pork shops and if they are ready to pay premium prices for safer products. This study used an experimental approach to determine consumer perception and assessment of improved pork shops and their willingness to pay (WTP) for pork products. A total of 152 respondents in two provinces in Vietnam joined in a Becker-DeGroot-Marschak (BDM) mechanism experiment to collect data on WTP for pork from typical and upgraded pork shops. A questionnaire was used to record consumer perception and assessment about the pork shops and products. Overall, consumers were willing to pay 20% more for upgraded fresh pork compared to what is currently available on the market. Consumers trusted in the effectiveness of the upgraded intervention and the quality of pork at the pork shop which increased their WTP for the upgraded pork. Concerns about contaminated pork had a negative impact on the WTP for typical pork, while high frequency of pork consumption and existence of elderly family members led to higher WTP for both products.. The findings indicate the potential economic benefit from upgrading pork shops, which would be an important driver to motivate sellers to improve food safety.